The position paper of the Polish Society of Allergology on climate changes, natural disasters and allergy and asthma - Pałczyński, Cezary; Kupryś-Lipinska, Izabela; Wittczak, Tomasz; Jassem, Ewa; Breborowicz, Anna; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
The observed global climate change is an indisputable cause of the increased frequency of extreme weather events and related natural disasters. This phenomenon is observed all over the world including Poland. Moreover, Polish citizens as tourists are also exposed to climate phenomena that do not occur in our climate zone. Extreme weather events and related disasters can have a significant impact on people with allergic diseases, including asthma. These effects may be associated with the exposure to air pollution, allergens, and specific microclimate conditions. Under the auspices of the Polish Society of Allergology, experts in the field of environmental allergy prepared a statement on climate changes, natural disasters and allergy and asthma to reduce the risk of adverse health events provoked by climate and weather factors. The guidelines contain the description of the factors related to climate changes and natural disasters affecting the course of allergic diseases, the specific microclimate conditions and the recommendations of the Polish Society of Allergology for vulnerable population, patients suffering from asthma and allergy diseases, allergologists and authorities in the event of climate and weather hazards.